(untitled) (Global Journal of Management and Business Research, 2021)
Taxation being the primary source of revenues to government is an important economic tool in attaining economic growth and sustainability. Thus, this research examines the position of taxation in Nigeria fourth republic economy. The study adopted a descriptive and historical research design; secondary data for nineteen years (1999 -2018) were collected from various issues of the Central Bank of Nigeria (CBN) statistical bulletin and annual reports. Tax revenue as an independent variable was measured with Direct taxes and indirect taxes and Nigerian economy measured using Real Gross Domestic Product. The data was analyzed using multiple regression analysis to establish the relationship between the dependent and independent variables. Durbin Watson test carried out and multicolinerity test using the VIF factor. From the study, we examined that, tax revenues are significant to economic growth in Nigeria. The study concluded that, direct taxes have positive relationship with economic growth and indirect taxes have negative relationship with Nigerian economy.